(untitled) (The Review of Diabetic Studies, 2025)
Background: Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) have emerged as one of the most effective pharmacological treatments for obesity and metabolic syndrome. Their pleiotropic mechanisms extend beyond glycemic control to appetite suppression, gastric emptying delay, and weight regulation. Objective: This systematic review synthesizes global and Saudi Arabian evidence on the efficacy, safety, and patient attitudes toward GLP-1 RAs, emphasizing their therapeutic potential in obesity management. Methods: Ten studies (2015–2026) were analyzed, including randomized controlled trials, cohort, and cross-sectional studies. Databases searched were PubMed, Scopus, Embase, Web of Science, and Google Scholar. Outcomes assessed included weight reduction, glycemic control, safety, tolerability, and awareness. Results: GLP-1 RAs demonstrated significant weight reductions ranging from 6% to 21%, with semaglutide and tirzepatide yielding the greatest effects. Improvements in HbA1c (−0.6% to −1.5%) and cardiometabolic parameters were consistent across trials. Saudi data revealed mean weight losses of approximately 8–10 kg and high patient satisfaction despite gastrointestinal side effects. Barriers such as cost and supply shortages were common. Conclusion: GLP-1 RAs are highly efficacious, safe, and well-tolerated for obesity management, with emerging local data supporting their use in Saudi Arabia. However, accessibility and patient education remain key limitations that need addressing to optimize public health impact.